FORCE MAJEURE CLAUSULES DUE TO COVID-19 IN BANK CREDIT AGREEMENTS - Permatasari, Pita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
Loan agreements usually contain clauses related to the rights and obligations betwen the debtor and creditor, but sometimes a force majeure clause is included if there is a situation beyond the will of the parties, such as natural disasters or war. The force majeure clause stipulated in Article 1244 and 1245 of Civil Code, in which there are for elements, first is there is an event that causes an achivement to be impossible, second is there is a cause that lies outside debtor’s fault, third is the causative factor was unexpected, and forth is the incident could not be blamed on the debtor. COVID-19 is considered a natioal disaster through the Presidential Decree of the Republic Indonesia Number 12 of 2020 dated April 13, 2020 concerning the Determination of the Non-Natural Disaster of The Corona Virus Desease 2019 (COVID-19) as National Disaster. Because of this, COVID-19 falls into category of relative or temporary force majeure. In addition, the government has made efforts to help the comunity, in this case UMKM actors who became debtors affected by COVID-19 by providing concessions for debtors to carry out kredit restructuring through the Finansial Services Authority Regulation Number 11/POJK.03/2020 Concerning National Economic Stmulus as Policy Countercyclical Impact of Coronavirus Disease 2019 Spread. The hope is to increase the resiliance of the debtor’s business in the midst of crisi due to the COVID-19 pandemic.